Alternative US History in Philip Dick’s Novel The Man in the High Castle (1962) and Philip Roth’s Novel The Plot Against America (2004) - Криницька, Наталія (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The paper gives a comparative analysis of Philip K. Dick’s novel The Man in the High Castle (1962) and Philip Roth’s novel The Plot Against America (2004) focusing on the role of the US national cultural mythology, primarily the American Dream, in the time of trials. Both works belong to the genre of alternative history with elements of dystopia and autobiography. The genre, plot and narrative peculiarities of these novels and the TV series The Man in the High Castle (2015–2019) are compared, namely: the alternative historical background of events, the subjective and objective factors of possibility of the World War II alternative retrospective suggested by the authors, the plot and narration in the novels. The alternative background (the success of a totalitarian Nazi project in the USA) is detailed in both novels, but Dick’s reality (the US occupation by the Axis countries and loss of national dignity) is more tragic than Roth’s reality, which shows a temporary deviation from the right course of his country that does not lead to the loss of independence. The structure of these works differs: multicultural polyphony with three worlds, six storylines and seven focalizers in Dick’s novel and linearity with a single focalizer and a focus on “The Jewish question” in Roth’s book, but both authors succeed in showing a convincing picture of a possible decline of humanistic and democratic projects. On the basis of such analysis, the problems of novels, in particular, the pitfalls of the American Dream are considered: mass consciousness, lack of critical thinking, consumerism, populism, pursuit of success, anti-Semitism, racism, xenophobia, over-enthusiasm for the “melting pot” concept, etc. The main method of restoring the American Dream for both authors is the proof by contradiction: by displaying global history through the local, they are gradually debunking totalitarian projects, which at first may seem very attractive, because they are based on the best myths and expectations of the mass society.